1964
DOI: 10.1161/01.res.14.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Oxygen Consumption During Ventricular Contraction and Relaxation

Abstract: • As early as 1915 it was known that an increase in systolic pressure is accompanied by a greater myocardial oxygen cost than a proportionate increase in stroke volume.1 Recent investigators have related myocardial oxygen consumption to the product of the mean systolic pressure and the heart rate, 2 or to the integral of systolic pressure in time. 3 In the isovolumetrically contracting ventricle, myocardial oxygen consumption could be equally well correlated with peak developed pressure, the integral of systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

1968
1968
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 9 publications
5
25
0
1
Order By: Relevance
“…Since both wall stress and the contractile state of the myocardium have been postulated to be important determinants of myocardial oxygen consumption (6,9), comparisons of oxygen consumption at different heart rates were made at matched levels of peak wall stress to minimize the effects of wall stress on oxygen consumption. Since Monroe (26) and others (27,28) have found that peak tension rather than the integrated tension is most closely related to MVo 2 , peak wall stress levels were matched in this study. This resulted in a marked reduction in integrated wall stress per beat at the higher heart rates, and it is possible that this reduction may have minimized the augmentation of oxygen consumption per beat observed at higher heart rates.…”
Section: Discussionmentioning
confidence: 58%
“…Since both wall stress and the contractile state of the myocardium have been postulated to be important determinants of myocardial oxygen consumption (6,9), comparisons of oxygen consumption at different heart rates were made at matched levels of peak wall stress to minimize the effects of wall stress on oxygen consumption. Since Monroe (26) and others (27,28) have found that peak tension rather than the integrated tension is most closely related to MVo 2 , peak wall stress levels were matched in this study. This resulted in a marked reduction in integrated wall stress per beat at the higher heart rates, and it is possible that this reduction may have minimized the augmentation of oxygen consumption per beat observed at higher heart rates.…”
Section: Discussionmentioning
confidence: 58%
“…6). The work of Monroe (50), demonstrating that over 90%o of the MVo2 was accounted for by the time peak tension was-reached, serves to emphasize the major energetic importance of tension development in contrast to the total developed tension (TDT), i.e., the area under the tension-time curve. Accordingly, in the present study, peak developed tension rather than total developed tension was held constant when Vmax was altered.…”
Section: Resultsmentioning
confidence: 99%
“…Monroe (34) observed that myocardial oxygen uptake was almost maximal by the time the peak systolic pressure had been reached and that peak systolic pressure could also be used to predict myocardial oxygen uptake. The increased coronary flow following distal aortic constriction was more closely associated with change in TTI than with this pressure in our studies so that we used TTI to estimate myocardial oxygen needs.…”
Section: Discussionmentioning
confidence: 99%